Experimental Study on Low Temperature Tensile Properties of Epoxy Mortar in Hydropower Project. (May 2017) - Huang, Hao; Hao, Jutao; Zhao, Bo; Zhao, Xinhua; Li, Meng; Li, Jingwei; Liu, Jiahong
Abstract: The surface protection of hydropower construction is directly related to the safety of the building itself and the security of energy supply. Epoxy mortar is widely used as protection material in the field of hydropower engineering, and its mechanical properties are greatly influenced by temperature and loading rate. Under the three tensile rates of 0.01 mm/min, 0.05 mm/min and 0.1 mm/min, and three test temperatures of 0 °C, –10 °C and -20 °C, the tensile strength, deformation modulus and ultimate tensile strain of epoxy mortar were obtained from tensile experiment. It was shown that the deformation modulus and tensile strength of epoxy mortar had little relationship to tensile rate, which is linear to temperature index, and the ultimate tensile strain had little relationship to both the tensile rate and temperature, which has laid a foundation for the study on low temperature stress and cracking mechanism of the surface protection material, and provides technical support for the application safety of hydropower energy.